Topical Tranexamic Acid Compared With Anterior Nasal Packing For Treatment of Anterior Epistaxis in Adults: A Randomized Controlled Trial (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Epistaxis is one of the common complaints in the emergency department. Anterior Nasal Packing (ANP) a frequently performed procedure in the management of epistaxis has many complications. The topical application of Tranexamic Acid (TXA) was found beneficial for the treatment ofanterior epistaxis. Objective of this study was to evaluate the role of topical tranexamic acid over anterior nasal pack in epistaxis management.Materials and methods: The study was a randomized controlled trial to compare the effect of topical TXA with ANP for treatment of anterior epistaxis conducted in the Department of Otolaryngology-Head and Neck Surgery of Chittagong Medical College Hospital (CMCH) Chattogram for a period of two years from February 2020 to January 2022. All adult patients admitted with epistaxis was the study population. A total of 220 patients (110 in each group) aged from 18 years and above with both genders were included as per selection criteria. Patients were followed up to control of epistaxis, then at 24 hours and finally from 24 hours up to 1 week from procedure. Fourteen patients were lost during follow up, eight from TXA group and six from ANP group. So, a total of 206 patients, 102 from TXA and 104 from ANP group were analyzed.Results: The mean age was 43.36±13.54 years inTXA group and 45.07±12.27 years in ANP group and was not statistically significant, p= 0.261. Number of male and female were 61 and 41 in TXA group andin ANP group were 52 and 52 (p=0.716). Mean bleeding arrest time in TXA group were 7.74± 3.28 minutes and in ANP group 9.28± 3.69 minutes (p value 0.004). Rebleeding within 24 hours was found in 6 patients in TXA group and 16 patients in ANP group (p value 0.045and risk coefficient 1.213). Overall treatment failure in TXA group was 11 and in ANP group was 30 (p value 0.0018). Mean length of hospital stay in TXA group was 24.71±2.84 hours and in ANP group was 27.92±8.92 hours (p value 0.000). Nasal Obstruction Symptom Evaluation (NOSE) score in TXA group was 24.95±4.9 and in ANP group was 66.92±5.96 (p value 0.000). Visual Analogue Scale (VAS) score in TXA group was 3.74±0.9 and in ANP group was 6.21±1.08 (p value 0.000).Conclusion: Topical TXA may be considered an effective treatment option for the management of anterior nasal epistaxis with less chance of re-bleeding, less discomfort and less duration of hospital stay.JCMCTA 2025; 36 (2) : 156-160